Catching-up process and public finances of Czechia and Hungary compared with Austria and the Netherlands in 2000-2018 - Mucha-Leszko, Bogumiła (Zmniejszanie luki gospodarczej i sytuacja w dziedzinie finansów publicznych Czech i Węgier w porównaniu z Austrią i Holandią w latach 2000-2018, 2019)
The subject of the paper is the analysis of economic growth and the situation of public finances in Czechia and Hungary in 2000-2018. The main research objective is to assess the effectiveness of the catching-up process, the budgetary policy and the situation in public finances in terms of the possibility to adjust economies to functioning in a common currency area and to orient budgetary policy towards stabilising economic growth while maintaining safe levels of public deficit and debt. The tools used in the analysis: deficit/ surplus and public debt in relation to GDP, GDP growth rates. In correlation analysis, the Pearson correlation coefficient was estimated. The reference countries for Czechia and Hungary are the Netherlands and Austria. The results of the analysis: Czechia and Hungary have achieved the highest GDP growth rates, Czechia and the Netherlands are the countries with the highest stability of public finances. Conclusions: (1) Czech fiscal policy was effective in terms of its capacity to adjust the economy to function in the single currency area and efficient in stabilising economic growth, (2) Hungary’s expansionary fiscal policy in 2001-2006 led to the collapse of public finances, but the plan to stabilise them was fulfilled
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 57-73